Management strategies of heterotopic pregnancy following in vitro fertilization-embryo transfer - Shangge Lv; Zhe Wang; Hailing Liu; Jin Peng; Jialun Song; Wei Liu; Lei Yan (Elsevier, 2020)
Objective: The purpose of this study was to evaluate the efficiency and safety of different treatment modalities for heterotopic pregnancy (HP) in vitro fertilization-embryo transfer (IVF-ET) cycles to avoid influence on intrauterine pregnancy (IUP). Materials and methods: Cases of HP (n = 90) were from the IVF/ICSI registry database at the Reproductive Hospital Affiliated to Shandong University. An additional 360 women were randomly selected as controls. The primary outcome to examine the risk factors, diagnostic modalities and the impact of different treatment modalities for HP. Results: Our results showed that surgical treatment had a certain effect on improving the live-birth rate, although the effect was not statistically significant (87.9% vs. 70.8%, P = 0.055). The risk factors for HP included previous tubal surgery and hydrosalpinx. Fourteen days after embryo transfer, the serum levels of β-human chorionic gonadotropin (β-hCG) and estradiol (E2) were lower in the HP group than in the IUP group (P < 0.05). Furthermore, age and endometrial thickness showed a significant difference between the early abortion and the live-birth groups of HP. Conclusions: In our retrospective study, we supported early surgical laparoscopic intervention to minimize the incidence of abortion of IUP, which resulted in a better live-birth rate. A history of ectopic pregnancy and previous tubal surgery may increase the risk of HP. Low levels of serum β-hCG and E2 on the 14th day after embryo transfer could indicate the incidence of HP. Keywords: Heterotopic pregnancy, IVF-ET, Surgery, Pregnancy outcome